Evolution of the Structure of Children's Morbidity Rate in the Republic of Sakha (Yakutia) - Tatyana E. Burtseva; Sardana A. Evseeva; Maya S. Savvina; Svetlana Y.Yakovleva; Vyacheslav G. Chasnyk (International Journal of Biomedicine, 2018)
Currently, the comparative studies of human health status definitely show that the health level of a population has a regional specificity. This paper analyzes the data of official medical statistics on morbidity among the child population in dynamics from 2000 to 2016 and presents the evolution of the children's incidence structure in the Republic of Sakha (Yakutia) (RS(Y)), according to ICD-10.